乾癬性顎関節炎に起因した両側顎関節強直症に対して関節授動術を施行した１例 - 森山, 雅文; 中村, 誠司; 田中, 翔一; 川野, 真太郎; 久保田, 英朗; 服部, 多市 (日本口腔外科学会雑誌, 2024)
Psoriatic arthritis (PsA) is a systemic inflammatory arthritis caused by psoriasis. We report the case of 32-year-old male was suffering from severe trismus due to PsA-related temporomandibular joint (TMJ) ankylosis. CT images showed that the bilateral condyle was completely fused to the glenoid fossa by bony ankylosis. Therefore, we performed an interpositional gap arthroplasty using a temporalis muscle fascia flap together with a coronoidotomy. The patient began jaw exercises one week after surgery, and by performing intermaxillary fixation using a bite plate with extra thickness in the molar area, the mandibular ramus height (gap) was maintained. The patient's maximum mouth opening increased significantly from 5 mm to 38 mm within two weeks of the surgery. Four years after the surgery, his maximum mouth opening was 32 mm and stable occlusion was maintained. According to a review of the literature, 66.8％ of PsA patients experienced a relapse of trismus and bony ankylosis after surgery. Based on our experience with this case and our review of the literature, we conclude that primary disease control via pharmacotherapy, gap arthroplasty and postoperative management may prevent a relapse for patients with PsA-related TMJ ankylosis.